Modeling vapor liquid equilibrium of ionic liquids + gas binary systems at high pressure with cubic equations of state - Freitas,A. C. D. (2013)
Ionic liquids (IL) have been described as novel environmentally benign solvents because of their remarkable characteristics. Numerous applications of these solvents continue to grow at an exponential rate. In this work, high pressure vapor liquid equilibria for 17 different IL + gas binary systems were modeled at different temperatures with Peng-Robinson (PR) and Soave-Redlich-Kwong (SRK) equations of state, combined with the van der Waals mixing rule with two binary interaction parameters (vdW-2). The experimental data were taken from the literature. The optimum binary interaction parameters were estimated by minimization of an objective function based on the average absolute relative deviation of liquid and vapor phases, using the modified Simplex algorithm. The solubilities of all gases studied in this work decrease as the temperature increases and increase with increasing pressure. The correlated results were highly satisfactory, with average absolute relative deviations of 2.10% and 2.25% for PR-vdW-2 and SRK-vdW-2, respectively.